The downfall of the American order? - Kat, Quintijn B (International Affairs, 2023)
This article discusses the end of the US-led liberal order and the factors that have contributed to its downfall. The authors analyze the evolution of the liberal order from post-1945 "embedded liberalism" to the fully unleashed neo-liberalism of the 1980s. They argue that the departure from Keynesian economics and the rise of market fundamentalism have led to the current crisis of the liberal order. The article also explores the role of identity, the abandonment of ideals by the left, and the emergence of anti-liberal populism. The authors conclude that while the American order may be ending, this does not necessarily mean the end of liberalism itself.